Sistematización de los principios Lean en la construcción del almacén ESPH - Ruíz-Guzmán, José Martín (Instituto Tecnológico de Costa Rica, 2012)
The present document contains methodologies and tools that facilitate the implementation of the Lean concepts in the administration project of construction. The philosophy Lean in the construction there has the aim to handle the processes of construction on lines of constant production, similar to the used ones in the companies of industrial production, so that the control of the flow of tasks is such that avoid a series of common problems of the constructive processes and that concern the time, the cost and the quality of the final product. The Lean philosophy stocks in such administrative technologies as Just in time, 5's, total quality control, reengineering etc the application of these technologies they have given important results to such companies as Toyota. For the development of this investigation there took the construction of the store ESPH, at the expense of construction AP, the above mentioned project served as base for the identification of the processes that are traditionally use in construction companies, identifying all the problems associated with the project. Once identified the weak points of the processes, they propose solutions based on the Lean concepts with the aim that they are applied in future projects, the above mentioned tools are focused in two point, the first one a detailed planning that predicts and avoids the occurrence of problems in process flow and secondly a system of control that guarantees the fulfillment of the planned goals.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Desperdicio; Just in time; Reingeniería; 5´s; Línea de producción